Loss of carbon stock as an impact of anthropogenic activities in a protected mangrove forest - SYAIFUL EDDY; ANDI ARIF SETIAWAN; MIRNA TAUFIK; MAHARANI OKTAVIA; BUDI UTOMO; NORIL MILANTARA (Society for Indonesian Biodiversity, 2023)
Abstract. Eddy S, Setiawan AA, Taufik M, Oktavia M, Utomo B, Milantara N. 2023. Loss of carbon stock as an impact of anthropogenic activities in a protected mangrove forest. Biodiversitas 24: 6493-6501. The significant anthropogenic activities within the mangrove forest, known as the Air Telang Protected Forest (ATPF) in the Banyuasin District, South Sumatra, Indonesia, have led to an alarming degradation, leaving only its primary mangrove forests, currently constituting approximately 26% of the total forest area. This study aims to analyze changes in land cover, quantify carbon reserve loss due to CO2 emissions, and assess carbon sequestration in the ATPF over two periods: 1999-2010 and 2010-2023. Remote sensing data for 1999, 2010, and 2023 were utilized from Landsat imagery, employing ENVI and ArcGIS for land cover classification. Carbon density, CO2 emissions, and carbon sequestration were analysed using the Land Use Planning for Multiple Environmental Services (LUMENS) software. The research findings reveal an increase in the primary forest area in the first period (by almost a quarter); however, more than half of this area was lost in the second period. The secondary forest area consistently decreased over the two periods, while the open area experienced significant growth. Carbon stocks in 2010 exceeded those in 1999 due to an increase in the primary forest area, but by 2023, carbon stocks decreased significantly due to extensive land clearing. The second period witnessed the largest emissions, exceeding those of the previous period by five times. Carbon sequestration in the first period surpassed that in the second period by more than three times, with the most significant sequestration resulting from the growth of secondary mangrove forests into primary mangrove forests. The study highlights the necessity of restoration and conservation of mangrove forest areas in ATPF for sustenance of its natural function as a protected forest.